2019
DOI: 10.59665/rar3615
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tillage and Crop Sequence Effects on Maize and Soybean Grain Yield Under Eastern Romanian Danube Plain Climate Conditions

Abstract: Much research around the world has compared the performance of maize (M) and soybean (S) grown under conventional and no tillage systems; however relatively few long-term experiments have been conducted in Eastern Romanian Danube Plain area. In 2012, an experiment was established at Fundulea – Romania, on cambic chernozem soil, testing two tillage treatments [no-tillage (NT) and chisel tillage (CT)], and two crop sequences [soybean (S) and winter wheat (WW) for maize and maize (M) and winter wheat (WW) for soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The difference between CS (8683 kg ha −1 ) and MTC (8653 kg ha −1 ) was not very high (138 kg ha −1 ), but the results showed that MTD and NT had a very significantly negative influence compared to CS, the yield differences being 1789 kg ha −1 and 2640 kg ha −1 , respectively. Similar research, but over a longer period, conducted by Cociu and Alionte [51] at Fundulea, showed that the average yield for eight years in the case of maize was significantly lower when CS (8820 kg ha −1 ) was applied rather than MTC (9050 kg ha −1 ). This is similar to Khan et al [52], who reported that a higher grain yield was established in NT crops than in CS crops.…”
Section: Maize Yield In Relation To Experimental Factorsmentioning
confidence: 55%
See 1 more Smart Citation
“…The difference between CS (8683 kg ha −1 ) and MTC (8653 kg ha −1 ) was not very high (138 kg ha −1 ), but the results showed that MTD and NT had a very significantly negative influence compared to CS, the yield differences being 1789 kg ha −1 and 2640 kg ha −1 , respectively. Similar research, but over a longer period, conducted by Cociu and Alionte [51] at Fundulea, showed that the average yield for eight years in the case of maize was significantly lower when CS (8820 kg ha −1 ) was applied rather than MTC (9050 kg ha −1 ). This is similar to Khan et al [52], who reported that a higher grain yield was established in NT crops than in CS crops.…”
Section: Maize Yield In Relation To Experimental Factorsmentioning
confidence: 55%
“…The irregular distribution of rainfall and high temperatures correlated with extended drought during the experiment period, specific to the area studied, and influenced the crop, including the quality indices [51]. Compared to the control variant, the starch content of grains (62.24% average for three years) fluctuated very significantly in two years (2020 positive, 2021 negative), and in 2019, it remained close to the control variant, at a difference of just 0.02%, which does not present statistical assurance.…”
Section: Maize Qualitymentioning
confidence: 97%